Toward a circular carbon economy: Production of green C1 compounds through high-temperature CO2 electrolysis - Nan Zheng; Jing Zhu; Haitao Zhu; Jin Xuan; Haoran Xu; Meng Ni (Nexus, 2025)
Summary: The electrochemical reduction of CO2 to value-added carbon-containing chemicals using solid oxide electrolysis cells presents a significant opportunity for mitigating carbon emissions and enabling a circular carbon economy. Within this context, single-carbon compounds are of particular interest due to their extensive applications as both chemical precursors and fuels. This review summarizes recent advancements in the conversion of CO2 to green methane and methanol through high-temperature electrolysis pathways. To enhance the efficiency and economic viability of this process, comprehensive system-level analysis has been conducted, focusing on system architecture, operational strategy refinement, and techno-economic assessment. The findings indicate that the integration of fluctuating renewable energy inputs can be effectively managed through strategic capacity allocation and energy management protocols. Additionally, modulating operational temperatures and the H2/CO ratio emerges as a promising, albeit challenging, approach to enhance product yields, given the complex kinetics of CO2 reduction. Furthermore, reducing the costs associated with electrolyzer fabrication and electricity consumption is identified as a pivotal factor for the commercial viability of this technology. There is a recognized need for further investigation into hydrogen-proton-conducting solid oxide electrolysis cells systems, particularly regarding the design of component assemblies and a more detailed techno-economic evaluation. Ultimately, this paper proposes a circular economy framework as an innovative solution to the resource challenges inherent in developing a sustainable, green infrastructure for the chemicals and energy sectors. Broader context: The carbon cycle economy is an approach that focuses on managing and reducing carbon emissions through a loop system that encompasses reducing, reusing, recycling, and removing. This approach is crucial in addressing the urgent need to reduce CO2 emissions and promote sustainable development. Converting captured CO2 into green C1 hydrocarbons via high-temperature electrolysis emerges as a multifaceted technology in the transition toward a circular carbon economy. This process not only mitigates the environmental, economic, and social challenges posed by climate change and our reliance on fossil fuels but also integrates high-efficiency electrolysis within the circular carbon economy framework. By doing so, it becomes feasible to reduce the carbon footprint across the chemicals and energy sectors without hindering economic progress. Therefore, a timely and comprehensive review of this topic is urgently desired to provide an in-depth understanding of the green system design.The review provides insights into the latest advancements in the conversion of CO2 to green methane and methanol through high-temperature electrolysis pathways. It offers insights into system design and operational strategies aimed at enhancing the safety and efficiency of these conversions. Furthermore, methods for reducing system costs and the conceptual integration of a circular economy model are explored, assessing its broader implications for sustainable development.